Project Phalanstère at Cac Brétigny or "Of museum orgy or mixed omnigamy in composite and harmonic order" treatise = Projet Phalanstère au Cac Brétigny ou "De l'orgie de museé ou omnigamie mixte en ordre composé et harmonique" : traite - Bal-Blanc, Pierre 1965-; Ouroumov, Émilie (Sternberg Press, 2017)
Organized by curator Pierre Bal-Blanc, the experimental architectural program "Project Phalanstère" consisted of a series of site-specific artworks in the Parisian suburbs. Taking place from 2003 to 2014, these projects developed a creative space extended in time. Here, in contrast with the duration of the work schedule, in which one task follows another, the simultaneity of life’s forces asserted its rhythm. Some works exceeded the conventional time and space of an exhibition: Lionel Estève’s myope et amnésique (2005), for example, was conceived to be larger than any one viewer can see; through the displacement of existing objects, both Cyprien Gaillard and Lois Weinberger reflected upon permanence and the monument; Christodolous Panayiotou and Jens Hanning made subtle alterations to existing architecture, playing with the material presence and experience of light; and so on.
800 Exemplare
Keywords: Geschichte 2003-2014; Installation -- Kunst; Paris -- Region